Herbicide-Resistant Invasive Plant Species Ludwigia decurrens Walter - Denny Kurniadie; Ryan Widianto; Dedi Widayat; Uum Umiyati; Ceppy Nasahi; Hisashi Kato-Noguchi (Plants, 2021)
Ludwigia decurrens Walter is a dicotyledonous plant belonging to the family Onagraceae. It is native to Central Eastern USA but has been spreading quickly and has naturalized in aquatic and riparian ecosystems (including rice paddy fields) in many countries; therefore, it is now considered an invasive noxious weed. L. decurrens is highly competitive with rice and causes a significant reduction in rice production. The objective of the present study was to evaluate the efficacy of the herbicide penoxsulam for the control of L. decurrens in rice fields. The seeds of L. decurrens were collected from four villages in Indonesia, and penoxsulam was applied to L. decurrens in seven dosages (0, 2.5, 5, 10, 20, 40, and 80 g a.i. ha−1) 3 weeks after seed sowing. The plant populations from Hegarmanah, Jatisari, and Joho showed complete mortality at the recommended dosage of penoxsulam (10 g a.i. ha−1). However, the plants from Demakan grew, flowered, and produced seeds 56 days after treatment with 40 g a.i. ha−1 of penoxsulam. The resistance index value of the population was 36.06. This is the first report of a penoxsulam-resistant weed from a dicotyledonous plant species and also the first report of a herbicide-resistant population of L. decurrens. The appearance of herbicide-resistant L. decurrens is a serious issue from both an environmental and an economic perspective, especially since protected forest and freshwater ecosystems are located at a short distance from the study area. Further research is needed to evaluate herbicide mixtures and/or the rotation of herbicide action sites. The identification of the penoxsulam-resistance mechanism in L. decurrens is also necessary to develop a herbicide resistance management strategy.